An automation test strategy based on real platform for digital control system software in nuclear power plant. (December 2020) - Xi, Wang; Liu, Wei; Bai, Tao; Ye, Wang-ping; Shi, Ji
Abstract: In nuclear power plant (NPP), the digital control system introduced nuclear safety software, whose fault tolerance and reliability directly affect the safety of nuclear power plant facilities. Current manual, simulation and testing strategies all have limitations. An effective method to test the system with software plays an important role to ensure the safe operation of NPP. In this paper, a digital control system software test strategy based on real platform is proposed. Taking the RPS system as an example, this strategy analyzes the system function and software logic path characteristics, then identifies the system state by threshold boundary analyzing, and designs a test method based on the random combination of logical combination paths and parameter value intervals, and builds a real platform test environment. This paper has tested the typical functions of Pressurized water reactor (PWR) protection system. The test results show that the test strategy has significantly improved the coverage of paths and parameters. Compared with manual testing, test efficient has been improved obviously in this test platform. At present, this strategy solves the problem of the low efficiency in manual testing, low real-level in simulation testing, and the insufficient coverage in simple automated testing strategy. This strategy also provides good practice for the control system testing and lays the foundation for the reliability evaluation of the system and software.